Given f(x)=2x+3 and g(x)=1/2(x-3), find the each composition. I am confuse how to set then up.

- anonymous

Given f(x)=2x+3 and g(x)=1/2(x-3), find the each composition. I am confuse how to set then up.

- Stacey Warren - Expert brainly.com

Hey! We 've verified this expert answer for you, click below to unlock the details :)

- schrodinger

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

- anonymous

a composition is f(g(x)) nd g(f(x)), where you substitute the whole other function for x

- anonymous

yeah,

- anonymous

you start from the inside to the outside, but i still confuse how to set them up.

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

- amistre64

f(g(x)) = 2(g(x)) + 3

- anonymous

f(x)=2x+3 and g(x)=1/2(x-3),
f(g(x) = 2(g(x)) + 3
f(g(x) = 2(1/2(x-3)) +3

- amistre64

g(f(x)) = 1/2(f(x)-3)

- anonymous

lol, amistre you fail

- amistre64

:) how so?

- anonymous

i just confuse, i need steps

- anonymous

you just write something them leave.

- amistre64

is there a time limt to wait around for a response? or am i allowed to come back after a response has been given? ;)

- amistre64

i figure with 352 medals, i might be doing something right lol

- anonymous

should we set one?

- anonymous

WB, which steps do you get? That'd be a good start

- anonymous

ok, so plz do step this time.

- anonymous

the beginning,

- amistre64

those are the steps; plug the one into the other; thats all there is to it.

- anonymous

what you plug?

- amistre64

f(x) = 2x+3 means that 'whatever' x equals, plug it in.
f(g(x)) simply means that x = g(x)

- anonymous

f(x)=2x+3 and g(x)=1/2(x-3),
f(g(x) = 2(g(x)) + 3
f(g(x) = 2(1/2(x-3)) +3
g(f(x)) = 1/2(f(x)-3)
g(f(x)) = 1/2(2x+3)-3)
then simplify by working out how to remove the parentheses

- amistre64

f(g(x)) = 2(g(x)) +3

- anonymous

ah, got it. thx tonks

- anonymous

all set, then I'm going to go now...jk ;)

- amistre64

f(w) = 2(x) + 3
f(4) = 2(4) + 3
f(applesause) = 2(applesauce) + 3
f(g(x)) = 2(g(x)) + 3 lol

- amistre64

...typed that lol

- anonymous

wait, i have a similar problem, bvut much harder.

- anonymous

the was just the start. and i got he answer, my prof did it on the board.

- amistre64

Tonks has it ;)

- anonymous

thx amistre

- anonymous

WB, post it as a new question, it is easier to find that way

- anonymous

f(x)=-7/2x -3
g(x)=-2x+6/7

- anonymous

this one is much harder.

- anonymous

WB, there's a new thread with this posted, check it out...

Looking for something else?

Not the answer you are looking for? Search for more explanations.